2012
DOI: 10.1038/bjc.2012.211
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between cellular components of the peritumoural inflammatory response, clinicopathological characteristics and survival in patients with primary operable colorectal cancer

Abstract: Background:The host inflammatory response is an important determinant of cancer outcome. We examined different methods of assessing the local inflammatory response in colorectal tumours and explored relationships with both clinicopathological characteristics and survival.Methods:Cohort study of patients (n=130) with primary operable colorectal cancer and mature follow-up. Local inflammatory response at the invasive margin was assessed with: (1) a semi-quantitative assessment of peritumoural inflammation using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
85
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(94 citation statements)
references
References 26 publications
(34 reference statements)
9
85
0
Order By: Relevance
“…Similar results have been reported in a variety of other cancers (12)(13)(14), suggesting that effective tumor immunity involves cooperative interactions between T cells and B cells. In our prior study (11), we found that CD8 þ and CD20 þ TIL often colocalized in lymphoid aggregates of various sizes and morphology.…”
Section: Introductionsupporting
confidence: 86%
“…Similar results have been reported in a variety of other cancers (12)(13)(14), suggesting that effective tumor immunity involves cooperative interactions between T cells and B cells. In our prior study (11), we found that CD8 þ and CD20 þ TIL often colocalized in lymphoid aggregates of various sizes and morphology.…”
Section: Introductionsupporting
confidence: 86%
“…In our study, we noted the lack of weak inflammatory infiltration in the invasive front and in center of the tumor in 50% of cases comparable to a medium or large infiltration in both locations (45-46%). Richards et al (18) reported a low-grade inflammatory cell infiltrate in 48% and high-grade inflammatory cell infiltrate in 52% cases in peritumoral stroma. We also noted low-TSP in 65% of cases and high-TSP in 35% of cases.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, authors showed that peritumoral inflammatory cell infiltrate was higher in advanced stage than in intratumoral densities. Also, Richards et al (18,26) demonstrated the presence of the relationship between the inflammatory cell infiltrate and pT status, positive lymph node status, TNM stage, venous invasion, necrosis and character of tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…6 The latter scheme has been demonstrated to be associated with survival of colorectal cancer patients in several studies. 6,11,22,23 Herein, Roxburgh et al 22 have compared both scoring systems and found an independent association with patients' survival in node-negative colorectal cancers only for the Klintrup-Mäkinen scheme. Furthermore, the inter-observer concordance was superior for the Klintrup-Mäkinen scheme.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Furthermore, the occurrence of eosinophil infiltration has been linked to the overall inflammatory cell reaction. 11 This raises the question whether the infiltration of eosinophils is a simple 'bystander' of an inflammatory host's reaction or might represent a selfcontained antitumoral mechanism that needs to be documented in routine pathology and promoted therapeutically?…”
mentioning
confidence: 99%